5x-(3x-6)=22

Simple and best practice solution for 5x-(3x-6)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(3x-6)=22 equation:


Simplifying
5x + -1(3x + -6) = 22

Reorder the terms:
5x + -1(-6 + 3x) = 22
5x + (-6 * -1 + 3x * -1) = 22
5x + (6 + -3x) = 22

Reorder the terms:
6 + 5x + -3x = 22

Combine like terms: 5x + -3x = 2x
6 + 2x = 22

Solving
6 + 2x = 22

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2x = 22 + -6

Combine like terms: 6 + -6 = 0
0 + 2x = 22 + -6
2x = 22 + -6

Combine like terms: 22 + -6 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| 7x+1=126 | | 6x^3=200 | | 8(2)+n=31 | | 1.4x+13.32=2.35x+21.92 | | (x-9)/7=3x | | 3-4(2x+7)=23 | | 10b-8=12b-10 | | 4(4/2+4)= | | 87+98+90+85=x | | -4(5x+2)=52 | | 8x+4(-4x+7)=34-8x | | x-9/7=3x | | x=43+86+51 | | 13m-21=9m-6 | | 7(2x-3)-3(5x+6)=-4(-3x+5)+5(-4x+5) | | 12-7b=18-9b | | 4x+8y=-44 | | ax+5=bx-cforx | | 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 | | 10-3c=10+9c | | 1x+7=2x+3 | | 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 |

Equations solver categories